Seeds and the Art of Genome Maintenance - Waterworth, Wanda M.; Bray, Clifford M.; West, Christopher E. (Frontiers in Plant Science, 2019)
Successful germination represents a crucial developmental transition in the plant lifecycle and is important both for crop yields and plant survival in natural ecosystems. However, germination potential decreases during storage and seed longevity is a key determinant of crop production. Decline in germination vigour is initially manifest as an increasing delay to radicle emergence and the completion of germination and eventually culminating in loss of seed viability. The molecular mechanisms that determine seed germination vigour and viability remain obscure, although deterioration in seed quality is associated with the accumulation of damage to cellular structures and macromolecules including lipids, protein, and nucleic acids. In desiccation tolerant seeds, desiccation/rehydration cycles and prolonged periods in the dry quiescent state are associated with remarkable levels of stress to the embryo genome which can result in mutagenesis of the genetic material, inhibition of transcription and replication and delayed growth and development. An increasing number of studies are revealing DNA damage accumulated in the embryo genome, and the repair capacity of the seed to reverse this damage, as major factors that determine seed vigour and viability. Recent findings are now establishing important roles for the DNA damage response in regulating germination, imposing a delay to germination in aged seed to minimise the deleterious consequences of DNA damage accumulated in the dry quiescent state. Understanding the mechanistic basis of seed longevity will underpin the directed improvement of crop varieties and support preservation of plant genetic resources in seed banks.